CEO Characteristics and Carbon Disclosure in Energy Sector: Moderating Stakeholder Pressure - Rajabanur Nanta Sari; Kamalah Saadah (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2026)
This study investigates the effect of CEO traits and stakeholder pressure Regarding the disclosure of carbon emissions in energy sector listed between 2020 and 2024 on the Indonesia Stock Exchange. Additionally, this study examines the moderating role of stakeholder pressure in the relationship between CEO characteristics as well as carbon emissions. Using a quantitative approach involving panel data regression and multiple linear regression with moderation analysis (MRA) to assess the moderating effect of stakeholder pressure by including an interaction term (CEO Characteristics × Stakeholder Pressure). this study analyzes 67 companies, resulting in 335 firm-year observations. The results show that CEO characteristics and stakeholder pressure have a positive and significant effect on carbon emission disclosure. However, stakeholder pressure does not moderate the relationship between CEO characteristics and carbon disclosure. The novelty of this study lies in integrating internal leadership factors and external stakeholder pressure within a moderating framework in the context of Indonesia’s energy sector. The findings support Upper Echelons Theory, indicating that internal leadership factors are more dominant in determining corporate environmental transparency.